Conservation agriculture for sustainable land use: the agronomic and environmental impacts of different tillage practices and plant residue retention : farmer uptake of reduced tillage in England - Alskaf, Kamal (2018)
Conservation Agriculture (CA) has potential benefits to the soil, crop yield, and the environment including reducing runoff, enhancing water retention and preventing soil erosion, in addition to increasing soil carbon sequestration and reducing greenhouse gas (GHG) emissions. Although CA is widely adopted in some areas of the world, it is still not widely adopted by UK farmers. The first overall aim of this project was to investigate the effects of tillage practice and residue retention, on soil physical properties, crop yield and GHG emissions. For this purpose, a split-plot field experiment was established on the University of Nottingham farm between September 2014 and August 2016. The main plot treatment was residue retention while cultivation practices were applied to the sub-plots and included three different tillage systems: no-tillage, minimum-tillage and deep ploughing. We used a novel analytical tool, X-ray Computed Tomography, to characterise the 3-D soil pore network in conjunction with a number of other soil physical properties such as bulk density, penetration resistance and shear strength. A range of portable chambers were used to detect the GHG emissions from soil and from soil-plant systems as influenced by the tillage and residue treatments. Winter wheat yield was not affected by the tillage treatments or residue retention in the first year, but, in the second year, no-tillage caused a 10% reduction in triticale yield compared to minimum-tillage and traditional ploughing. Multiple regression analysis showed that the lower triticale yield was partially explained by higher soil strength in the no-tillage plots, together with lower soil moisture content in summer. Our results show that while there is potential for climate change mitigation from no-tillage when the Net Ecosystem Exchange is considered, this effect could not be observed from soil emissions only. The second aim of this project was to assess the current level of reduced tillage (RT) uptake by UK farmers and the constraints for further adoption. A postal questionnaire was conducted in January 2016. This questionnaire found that only 7.0% of the arable land in England is under no-tillage and 47.6% is under minimum-tillage. The adoption of RT increased with an increase in farm size as it was the most adopted on farms >400 ha. Moreover, RT was adopted most on combinable crop farms. Weed management and slugs were identified as main challenges for RT adopters. Increasing uptake of CA from current levels will probably require policy intervention including financial incentives for growers during the early stages of the transition from ploughing to CA. This will encourage farmers to buy RT equipment and may help them to cover any potential yield reduction, if occurred, before the CA system stabilisation.